KETAHANAN PANGAN RUMAH TANGGA PETANI KOPI DI KECAMATAN ULU BELU KABUPATEN TANGGAMUS - Anggitasari, Elok Dinar; Indriani, Yaktiworo; Prasmatiwi, fembriarti Erry (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The aims of this research are to analyze the level of food security, the factors that affect the level of food security, and efforts to increase the level of food security of coffee farmer households. The method used in this research is a survey method. Location is chosen purposively in Ngarip and Sukamaju Villages, Ulu Belu Subdistrict, Tanggamus regency with samples of 70 coffee farmer households selected using a simple random method. The data were primary and secondary data, collected in May - July 2018 and analyzed by cross-table between the share of food expenditure and energy adequacy level, ordinal logistic regression, and descriptive qualitative analysis. The results of the research according to BPS showed that the majority of respondents belonged to the category of food secure (31.43%), and the rest belonged to the category lack of food (30.00%), food vulnerable (22.86%), food insecure (15.71%). The results according to nutrition and 2012 food law showed that the majority of respondents belonged to the category of food security (50.00%), lack of food (41.43%), food vulnerable (5.71%), and food insecure (2.86%). The affecting factors on the level of food security were the household income and education level of housewives. The efforts to increase the level of food security by Government were conducted by monitoring of food availability and food reserves, developing food distribution and stabilization of food prices, developing diversification of consumption and food security as well as staple food assistance through the raskin program, whereas efforts are carried out by households coffee farmers, namely by doing productive activities outside the coffee farm. Key words: coffee farmer households, food expenditure, food security